Kaitan Pandangan Aliran Filsafat Progresivisme terhadap Siswa Slow Learners dalam Proses Pembelajaran - Septi Nur Fauziya; Tian Abdul Aziz (Griya Journal of Mathematics Education and Application, 2022)
This article contains the relationship between the views of the philosophy of progressivism towards slow learners in the learning process. Slow learners are students who have a slower learning process with an average IQ score of around 70 – 90. As a teacher, we need to pay more attention to slow learners so they can maximize their learning abilities and explore their potentials. This article uses library research methods, which conducted by using literature (library), in the form of books, notes, or other reference sources. Therefore, the philosophy of progressivism education is an understanding that makes learning meaningful and not authoritarian learning which requires students to master all the learning materials provided. There are five links between slow learners and the flow of progressivism education philosophy, as follows: (1) times, slow learners need more time to study the material given by the teacher; (2) giving problems related to everyday life, slow learners are given lessons in accordance with real examples so they are easy to imagine; (3) giving awards, awards given to slow learners can increase their motivation in learning; (4) learning with audio and visual media, which can strengthen and attract slow learners’ attention during learning process; and (5) review, reviewing learning process will strengthen their memory in remember the lessons that have been given.